2011
DOI: 10.1155/2011/294394
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Preference ofGammarus pulexandAsellus aquaticusduring a Laboratory Breeding Programme for Ecotoxicological Studies

Abstract: An investigation was undertaken to establish if Gammarus pulex and Asellus aquaticus preferred a diet of unconditioned, artificially or naturally conditioned alder leaves (Alnus glutinosa). Standardised, 24 hour ex situ feeding assays were undertaken with both species to determine their food preference. The results showed that A. aquaticus ate more leaf material compared to G. pulex (Z 23.909, P 0.001) when exposed to all three test variables. Also, both G. pulex and A. aquaticus demonstrated a preference for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Leaves were conditioned in stream water for two weeks at 15 °C, which allowed the leaching of soluble components, softening, and encouraged fungal growth (Bloor 2011). Leaves were cut into 6 mm-diameter leaf discs using a cork-borer, with midribs and any obvious infected areas avoided, and these were then air-dried, sorted into batches of five, and weighed (leaf batch air-dry mass = 16.00 ± 3.27 mg, n  = 320).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaves were conditioned in stream water for two weeks at 15 °C, which allowed the leaching of soluble components, softening, and encouraged fungal growth (Bloor 2011). Leaves were cut into 6 mm-diameter leaf discs using a cork-borer, with midribs and any obvious infected areas avoided, and these were then air-dried, sorted into batches of five, and weighed (leaf batch air-dry mass = 16.00 ± 3.27 mg, n  = 320).…”
Section: Methodsmentioning
confidence: 99%
“…Leaves of the sycamore tree ( A. pseudoplatanus ) were provided as the food source, as this tree is common at the collection sites of both species and its leaves have been shown to be highly palatable to amphipods (MacNeil and Platvoet 2005 ). Leaves were conditioned in stream water for two weeks at 15 °C, which allowed the leaching of soluble components, softening, and encouraged fungal growth (Bloor 2011 ). Leaves were cut into 6 mm-diameter leaf discs using a cork-borer, with midribs and any obvious infected areas avoided, and these were then air-dried, sorted into batches of five, and weighed (leaf batch air-dry mass = 16.00 ± 3.27 mg, n = 320).…”
Section: Methodsmentioning
confidence: 99%
“…The number of α-amylase genes is also variable in non-decapod crustaceans. For instance, six copies of the α-amylase gene occur in the detritivore isopod Asellus aquaticus [48], which eats on leaf material in freshwater environments [49], while two copies in other detritivore isopod, Sphaeroma serratum [48], which fed on detritus from marine algae or terrestrial plants [49], although its fatty acid signature suggested that animal material is also included in its natural diet [49]. In other arthropods this issue has been studied more thoroughly.…”
Section: Gene and Transcript Featuresmentioning
confidence: 99%
“…In the laboratory, pairs were separated and each individual was placed in a transparent plastic container of 100 ml of water from the collection site at 4°C with a 1-cm 2 piece of rotted oak leaf as a food source (Bloor 2010). Each day, the water was replaced with new filtered river water, taken from the sample site at low tide, preventing the G. zaddachi from feeding on their own faeces or on any algae or microbial biofilms accumulating in the storage containers (Bloor 2010(Bloor , 2011.…”
Section: Collection and Maintenancementioning
confidence: 99%